Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
\(abc-\left(ab+bc+ca\right)+\left(a+b+c\right)-1\\ =abc-ab-bc-ac+a+b+c-1\\ =\left(abc-ab\right)-\left(bc-b\right)-\left(ac-a\right)+\left(c-1\right)\\ =ab\left(c-1\right)-b\left(c-1\right)-a\left(c-1\right)+\left(c-1\right)\\ =\left(c-1\right)\left(ab-b-a+1\right)\\ =\left(c-1\right)\left[\left(ab-b\right)-\left(a-1\right)\right]\\ =\left(c-1\right)\left[b\left(a-1\right)-\left(a-1\right)\right]\\ =\left(c-1\right)\left(b-1\right)\left(a-1\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(ab\left(a+b\right)+bc\left(b+c\right)+ca\left(c+a\right)+2abc\)
\(=ab\left(a+b\right)+abc+bc\left(b+c\right)+abc+ca\left(c+a\right)\)
\(=ab\left(a+b+c\right)+bc\left(b+c+a\right)+ca\left(c+a\right)\)
\(=\left(a+b+c\right)\left(ab+bc\right)+ca\left(c+a\right)\)
\(=b.\left(a+b+c\right)\left(a+c\right)+ca\left(c+a\right)\)
\(=\left(a+c\right)\left[b.\left(a+b+c\right)+ca\right]\)
\(=\left(a+c\right)\left(ab+b^2+bc+ca\right)\)
\(=\left(a+c\right)\left[a\left(b+c\right)+b\left(b+c\right)\right]\)
\(=\left(a+c\right)\left(b+c\right)\left(a+b\right)\)
\(ab\left(a+b\right)+bc\left(b+c\right)+ca\left(c+a\right)+3abc\)
\(=ab\left(a+b\right)+abc+bc\left(b+c\right)+abc+ca\left(c+a\right)+abc\)
\(=ab\left(a+b+c\right)+bc\left(b+c+a\right)+ca\left(c+a+b\right)\)
\(=\left(a+b+c\right)\left(ab+bc+ac\right)\)
Tham khảo nhé~
![](https://rs.olm.vn/images/avt/0.png?1311)
= (abc - ab) + (a - ca) + (b - bc) + (c -1) = ab.(c -1) - a.(c - 1) - b(c -1) + (c -1) = (c -1).(ab - a - b + 1)
abc-(ab+bc+ca)+(a+b+c)-1
=abc-ab-bc-ca+a+b+c-1
=(abc-ab)+(-bc+b)+(-ca+a)+(c-1)
=ab.(c-1)-b.(c-1)-a.(c-1)+(c-1)
=(c-1)(ab-b-a+1)
=(c-1)[b.(a-1)-(a-1)]
=(c-1)(a-1)(b-1)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(ab\left(a+b\right)-bc\left(b+c\right)+ca\left(a+c\right)+abc\)
\(=a^2b+ab^2-b^2c-bc^2+ca^2+c^2b+abc\)
\(=a^2b+ab^2-b^2c+a^2c+abc\)
Đến đây thì mk chịu
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
sửa đề thành \(ab\left(a+b\right)+bc\left(b+c\right)+ca\left(c+a\right)+2abc\)
\(=ab\left(a+b\right)+b^2c+bc^2+c^2a+ca^2+2abc\)
\(=ab\left(a+b\right)+\left(b^2c+abc\right)+\left(c^2a+c^2b\right)+\left(a^2c+abc\right)\)
\(=ab\left(a+b\right)+bc\left(a+b\right)+c^2\left(a+b\right)+ac\left(a+b\right)\)
\(=\left(a+b\right)\left(ab+bc+a^2+ca\right)\)
\(=\left(a+b\right)\left[\left(ab+bc\right)+\left(c^2+ac\right)\right]\)
\(=\left(a+b\right)\left[b\left(a+c\right)+c\left(c+a\right)\right]\)
\(\left(a+b\right)\left(b+c\right)\left(c+a\right)\)